MANAJEMEN PENGELOLAAN LIMBAH INDUSTRI - Muhammad Nasir; Edy Purwo Saputro; Sih Handayani (Benefit: Jurnal Manajemen dan Bisnis, 2015)
Industrial waste is one of serious problems in the industrialization era. Hence the waste management must be addressed early during the production process. It means that waste treatment process should be performed from upstream to downstream. This study aims to establish an optimization model of waste management with quantitative analysis that is conducted through focus group discussions and in-depth interview that combine voice of producer and voice of costumer. The result shows there are many aspects related to waste from tahu industry in Kartasura, then it makes the optimization of the waste to be very important. The result of this study is not able to solve all the problems, then there are limitations and further researches, and advice is needed for this study.